Resistance Toward Subordination of Women in The Breadwinner Novel by Deborah Ellis: A Feminist Study - Salsabila, Firdha; Panjaitan, Esterria Romauli; Mandela, Fitra (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
This research aimed to discover the resistance and the subordination forms. The method used is descriptive qualitative research method and feminism approach applied specifically Simone de Beauvoir's notions of The Otherness in The Second Sex book. The data gathered through attentive reading and observation of the narration, mono – dialogue, and characters' actions in The Breadwinner novel by Deborah Ellis. Furthermore, the writers determined that women have a difficult access to work as a result of discrimination and exploitation, married women are required to be completely subservient to their husbands, unequal education opportunity, parents expected a son over a daughter, and women unable to participate in social-political activities. Also, on Beauvoir ideas of resist toward The Otherness such as women can work, become intellectuals, contribute to a socialist revolution, and women can transcend their limitations by refusing to internalize their otherness or to identify themselves through the dominant group's eyes. This can be concluded that women still faced severe discrimination, oppression, exploitation, and inequality to gain their freedom, yet women still resist to the oppression in society.